FAO economics expert Miss Mary Ross working in the Egyptian Nile delta to raise the standard of living of the rural population - Morin, Patrick, (1954)
FAO economics expert Miss Mary Ross working in the Egyptian Nile delta to raise the standard of living of the rural population.